Rheological comparison between control and Dupuytren fibroblasts when plated in circular micropatterns using atomic force microscopy - Pérez-Domínguez, Sandra; Werkmeister, Elisabeth; Marini, Maria Luisa; Dupres, Vincent; Janel, Sébastien; Lafont, Frank; Radmacher, Manfred (Frontiers in Physics, 2022)
In tissue, cells are obliged to confine and adapt to a specific geometric shape due to the surrounding environmental constraints. Under healthy conditions, fibroblasts present an elongated shape; however, changes in biochemical and physical properties of the extracellular matrix could distort the cell shape, inducing a pathological state. We have studied fibroblasts’ mechanical behavior under circular geometrical constraints. Circular micropatterns force fibroblasts to acquire a different shape from that of a healthy tissue, inducing a possible pathological condition. In total, three different fibroblast types from Dupuytren’s disorder, all obtained from the same patient, were confined in circular-shaped micropatterns of three different diameters (25, 35, and 45 µm), and mechanical properties were evaluated using an atomic force microscope (AFM). We found that control fibroblast mechanics (apparent Young’s modulus) increases with the increasing pattern diameter and comes together with a decrease in cell height and in loss tangent, translated into a more solid-like behavior. We hypothesize that these results resemble the transition toward the myofibroblast phenotype, ameliorating cytoskeleton formation and organization and enhancing cell contraction. Scar and Dupuytren fibroblasts did not display major changes in cell mechanics and cell height when changing the pattern diameter, suggesting that they are less affected by physical changes in the environment as they can adapt their shape to the geometrical dimensions. Therefore, our findings demonstrate that combining micropatterning and AFM measurements provides a powerful tool to study cell mechanics inducing constraints onto the cell, thus mimicking certain aspects of the tissue environment in both healthy and pathological states.